Graphene coatings for the mitigation of electron stimulated desorption and fullerene cap formation - Bachmatiuk, Alicja; Dianat, Arezoo; Ortmann, Frank; Quang, Huy Ta; Cichocka, Magdalena Ola; Gonzalez-Martinez, Ignacio; Fu, Lei; Rellinghaus, Bernd; Eckert, Joergen; Cuniberti, Gianaurelio (Giovanni); Ruemmeli, Mark Hermann (Chemistry of Materials, 2014)
Graphene already has numerous applications in transmission electron microscopy. Here, we extend its application in electron microscopy by demonstrating its potential to stop electron induced desorption in nonconducting samples, where in essence charge build-up leads to surface atom desorption. Graphene films provide a conduction pathway to prevent charge build-up and do not interfere with the imaging process allowing the direct imaging of specimens sensitive to electron induced desorption. We also show that small graphene flakes on the surface of MgO transform to fullerenes or hemispherical fullerenes. The hemispherical fullerenes anchor to the MgO surface and are of particular interest as they suggest it should be possible to nucleate single walled carbon nanotubes on the surface of oxide supports without the need of a catalyst particle.
CRIS-Team Scopus Importer:2023-03-20